Influence of financial literacy on the investment decisions of small and medium enterprise owners - Donggon, Gellian; Felicitas, Catherine; Senerez, Mary Shinneth; Petalcorin, Cedric Ian Carlo (Business and Organization Studies e-Journal, 2024)
Financial literacy is enhancing the nation's financial progress and promoting economic growth. In light of these changes, it is crucial to evaluate if the latest generation, especially small and medium-sized firms (SMEs), considered the principal investors, drivers, and catalysts of the economy, has the necessary comprehension of financial principles. This research identified the area of financial literacy that strongly impacts the investment choices of SMEs in Davao City. The researchers used the descriptive-correlation approach to investigate the impact of financial literacy on the investment choices of SMEs. The study participants were owners, managers, accountants, or anyone having legal capacity to represent SMEs in select barangays in Davao City, totaling one hundred and seven (107) respondents. The data was gathered, analyzed, and interpreted using statistical techniques like mean, standard deviation, Pearson correlation, and regression analysis. SME owners need enhanced financial literacy and improved investment decision-making capabilities. The research demonstrated a substantial correlation between financial literacy and investment decisions. Regression analysis showed that financial literacy, personal characteristics, financial knowledge, and awareness are important predictors of investing choices. The results of this research indicate the need of participating in seminars, workshops, and awareness programs that identify the warning indications of investment fraud. It will assist SME owners in improving their financial literacy and enable them to differentiate between legal investment possibilities and fraudulent scams.